Unilateral Linear Punctate Palmoplantar Keratoderma: A Case Report - Chanisa Kiatsurayanon; Jinda Rojanamatin; Poonawis Sudtikoonaseth; Kowit Kampirapap; Mingkwan Wichaidit; François Niyonsaba (Karger Publishers, 2017)
Punctate palmoplantar keratoderma (PPPK) is a rare entity with an estimated prevalence rate of 1.17/100,000. PPPK usually presents with bilateral asymptomatic, tiny, hyperkeratotic punctate papules and plaques on the palmoplantar surface. Among the PPPK varieties, the linear presentation is much rarer, and so far there have been only 3 case reports. Here, we report the case of a 27-year-old female Thai patient who presented to our outpatient clinic with unilateral asymptomatic linear thickening lesions on her right sole since childhood. There were no similar lesions on other parts of the body. A histopathologic examination revealed epidermal hyperplasia and hyperkeratosis without columns of parakeratosis or cornoid lamella. The other examinations were normal. The clinical and histological contexts were consistent with a diagnosis of unilateral linear PPPK. The patient was treated with topical 10% urea cream and 10% salicylic acid cream twice daily. To the best of our knowledge, this is the first reported case of unilateral linear PPPK in Thailand, and the fourth reported case worldwide.